Shopaholic to the rescue ebook A novel. - Kinsella, Sophie (Shopaholic, 2015)
The #1 New York Times bestselling author of The Party Crasher and Love Your Life returns with another laugh-out-loud Becky Brandon (née Bloomwood) adventure: a hilarious road trip through the American West to Las Vegas.   “Sophie Kinsella keeps her finger on the cultural pulse, while leaving me giddy with laughter.”—Jojo Moyes, author of The Giver of Stars and The Last Letter from Your Lover Becky is on a major rescue mission through the American West to Las Vegas! Her father has vanished from Los Angeles on a mysterious quest with the husband of Becky’s best friend, Suze. Becky’s mum is hysterical; Suze is flat-out desperate. Worse, Becky must tolerate an enemy along for the ride, who she’s convinced is up to no good. Determined to get to the bottom of why her dad has disappeared, help Suze, contain the dreaded Alicia, and reunite her fractured family, Becky knows that she must marshal all her trademark ingenuity. The result: her most outrageous and daring plan yet!   But just when her family needs her more than ever, can Becky pull it off? Praise for Shopaholic to the Rescue “Full of gags, sparkling dialogue and beautifully drawn characters . . . It’s a real treat to be reunited with the eminently loveable, incredibly ditzy and fiercely loyal Shopaholic protagonist Becky Brandon (née Bloomwood).” — Daily Mail “Will Bex and best friend Suze ever make up? Will Becky’s old nemesis, banker Derek Smeath, finish his memoir? Why can’t our beloved Shopaholic seem to spend any money, even on a $2.50 pencil? . . . This is escapism that will make you giggle out loud.” —USA Today   “Readers can’t help but be delighted. Kinsella never once loses Becky’s voice and heart, which is one of the joys of the Shopaholic series.” —Publishers Weekly “Full of Becky’s outrageous ideas, including a heist à la Ocean’s Eleven, this novel does not disappoint. . . . Kinsella adds a mystery and twists and turns at every corner in this latest work while maintaining Becky’s signature voice.” —Library Journal